(3fbhd eNJdaIs
(3ChdgG (B:s
(3GdMeO ddg efRd GddZGJ hGdcJGH CeG HYO MeOkG ddg ejSQ CSHGH GdfLGM s
(3BNQgG (B:s
(3hbO hUd eG CJMa Hg ef GdgOjI GdSfjI GdHgjI, hbhHdJ HGdbHhd, hGddg jHdZ ebGeg GdYGdj ZGjI GdeCehd Hefg hcQeg s
(3HgG fXGe GdJYbjHIs
(3GdfSNI ajgG VHWs
(3efgG ef EfTGA TgGH GdOjf CHj GdKfGA eMehO, hGdUaOj, hGHf fHGJg hGHf RjOhf, hGHf ecGfS, hJbj GdOjf Hf MLg, hGHf GdCKjQ, hZjQges
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B164 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs